Dsb-insensitive expression of CcrA, a metallo-beta-lactamase from Bacteroides fragilis, in Escherichia coli after amino acid substitution at two cysteine residues within CcrA. - Elksne, L E (1996)
It has previously been shown that functional expression of CcrA, a metallo-beta-lactamase from Bacteroides fragilis, in Escherichia coli requires a mutation in either dsbA or dsbB, components of a periplasmic disulfide bond-catalyzing system. Site-directed mutagenesis resulting in the substitution of various amino acids for two of the three cysteine residues within CcrA allowed the expression of CcrA in a dsb+ background. This finding supports the hypothesis that DsbA creates aberrant disulfide bonds involving the Cys residues of CcrA.